The Influence of Jigsaw Cooperative Learning Model on Learning Outcomes of Biology Protist Material - Liunima, Imbred Rionard; Taek, Paulus (Haumeni Journal of Education, 2024)
The time of the research was carried out in July-July 2023. The aim of this research was to determine the effect of the jigsaw cooperative learning model on the learning outcomes of students at SMA Negeri 1 Amanuban Tengah. This research is Quasi Experimental which consists of 2 classes. The instruments used in this research are: RPP, Student Worksheets (LKPD) and learning media, The data collected is a learning outcomes test. The data collection technique in this research used multiple-choice tests, pretests, and posttests. The data analysis technique used is the t-test. The research results showed that the average pre-test control learning result score was 27.53 and the post-test score was 48.92, while in the experimental class, the average pre-test score was 27.38 and the post-test score was 64.30. The analysis uses all posttest results and is tested using the t-test with the calculated t < t table (0.009 < 0.05) showing that Ho is rejected and Ha is accepted, from these results it can be concluded that the learning outcomes of students using the Jigsaw model have better learning outcomes than the learning outcomes of students using the Lecture model